ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUI PEMILIHAN METODE AKUNTANSI PERSEDIAN (studi pada perusahaan manufaktur yang terdaftar di Bursa Efek Indonesia) - Nailul Rahmi; Anik Malikah; Junaidi Junaidi (Universitas Islam Malang, 2018)
Abstract:This study aims to analyze the selection of inventory accounting methods. Todetermine the selection of the inventory valuation method, the Company is requiredto comply with the Statement of Financial Accounting Standards (PSAK), ie PSAKNo. 14 (2008) to regulate the accounting treatment of inventories, stating that thecompany may only choose the inventory accounting method that is FIFO (First infirst out), or average. This is aligned by the taxation of Article 10 paragraph 6 of theIncome Tax Law. Sampling technique using purposive sampling method obtained 54companies. Methods of data analysis using logistic regression. The dependentvariable is expressed by dummy variable that is 0 for firms using FIFO method andnumber 1 for companies using AVERAGE method. The population in this study areall manufacturing companies listed on the Indonesia Stock Exchange period 2014-2017. Sampling technique using purposive sampling method obtained 54 companies.Methods of data analysis using logistic regression. The results of this study indicatethat the simultaneous variability of inventory, firm size, and current ratio affect theselection of inventory accounting methods on manufacturing companies listed on theIndonesia Stock Exchange while the partial test results show that inventoryvariability, firm size and current ratio partially affect the selection inventoryaccounting methods.Keywords: Inventory Variability, Company Size, Current Ratio, inventory valuationmethod.